Markeringsangivelser i ordböcker: några strukturella aspekter - Svensén, Bo (Nordiske Studier i Leksikografi, 2001)
This contribution deals with some structural aspects of diasystematic marking in dictionaries. The functions and structural properties of the markers themselves are discussed as well as their relationship to other textual elements, applying the conceptual and terminological framework used in Nordisk leksikografisk ordbok [Nordic Dictionary of Lexicography]. In the concluding section, some problems pertaining to the user aspect are briefly touched upon.